Antimicrobial resistance and genotyping of Mycobacterium leprae in Venezuela - Sisco, Maria Carolina; Brum Fontes, Amanda N.; Lessmann, Lucibel Crespo; Rada, Elsa; Prado Palacios, Yrneh Y.; Vasconcellos, Sidra E. G.; de Waard, Jacobus H.; Suffys, Philip N. (Frontiers in Tropical Diseases, 2023)
Leprosy is a neglected disease that leads to physical disability and social discrimination. The active surveillance of new cases and vigilance of drug resistance can decrease the incidence and improve the clinical outcome of people affected by the disease. We analyzed, with molecular biology techniques, a set of skin biopsy samples from 25 Venezuelan patients. The patients were diagnosed with leprosy in 2014 and early 2015, and 15 were relapse cases. The samples were tested for molecular drug resistance to dapsone, rifampicin, and fluoroquinolones. Additionally, we performed molecular epidemiology analysis through MLVA and SNP typing. We did not find evidence of drug resistance and 76% of the samples (n=16) had isolates belonging to SNP 3. Genotyping profiles allowed us to discard re-infection in a patient with persistent symptoms after treatment and rule out household transmission in two more patients. Although our sampling is relatively small, very similar or even identical M. leprae genotypes were observed in Miranda State; highly suggestive of local higher transmission and need for a better control of the disease. Finally, the copy number distribution of minisatellite 18-8 in a considerable number of SNP type 3 strains strongly suggests the presence of a particular sub-lineage in Venezuela.